Numerical simulation of stand-alone photovoltaic integrated with earth to air heat exchanger for space heating/cooling of a residential building. (February 2023) - Anshu, Kumari; Kumar, Prashant; Pradhan, Basudev
Abstract: Earth-to-air heat exchanger is one of the efficient energy-saving approaches to meet the heating/cooling requirement of residential buildings/greenhouses. In this work, a comprehensive numerical and statistical approach using the response surface method aiming at the integration of stand-alone photovoltaics with earth-to-air heat exchangers is discussed for the coordinates of Delhi. For parametric optimization of the earth-to-air heat exchanger, statistical tool, and response surface methodology is used by taking ground temperature profile and weather data into account. Among the primary parameters, the diameter of the pipe is found to be the most significant parameter. Optimized pipe diameter of 0.2 m, pipe length of 70 m, and air velocity of 7 m/s have yielded a total energy gain of 8116.7 kWh/year. Evaluation of herein designed hybrid system has estimated CO2 mitigation of 16.18 tons/year which in turn has evinced the carbon credit value to US 336.86/year. Calculations exhibit a simple payback period of approx. 5 and 10 years for one day and 2 days autonomy respectively when compared with the electricity cost of diesel generators for rural areas. With 24 h grid availability, the simple payback period with a photovoltaic system gets reduced to 4–5 years in urban areas as it doesn't require any battery bank. This kind of self-sufficient hybrid system is an eco-friendly and sustainable energy solution for altogether rural and urban areas. This work provides an effective blueprint of commercially viable photovoltaic integrated with earth-to-air heat exchanger systems for households. Graphical abstract: Image 1